2017
DOI: 10.5617/oslaw2769
|View full text |Cite
|
Sign up to set email alerts
|

The Legal Treatment of Muslim Minority Women under the Rule of Islamic Law in Greek Thrace

Abstract: The treatment of women in the frame of Islam has become subject to lively debate, lately concentrated in domains of the West where Islamic law seeks recognition without Islam being the prevailing creed. The discussions often are focused on concerns whether Muslim women are confronted with discriminative treatment and impediments to their access to justice. In this context, Greece occupies a unique position. Greece constitutes the only European State that recognises officially a special Islamic jurisdiction. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…If we consider discussions about Greek legal system that is based on legal pluralism, both of supportive and oppositional arguments are asserted. First of all, normative structure of religious tribunals is repeatedly criticized for failing to protect Muslim women's rights 30 . Also, Greek legal pluralism is regarded as institutional remnant of pre-modern State structure and inconsistent with cultural diversity and post-modern legal pluralism.…”
Section: The Discussion On Legal Pluralismentioning
confidence: 99%
“…If we consider discussions about Greek legal system that is based on legal pluralism, both of supportive and oppositional arguments are asserted. First of all, normative structure of religious tribunals is repeatedly criticized for failing to protect Muslim women's rights 30 . Also, Greek legal pluralism is regarded as institutional remnant of pre-modern State structure and inconsistent with cultural diversity and post-modern legal pluralism.…”
Section: The Discussion On Legal Pluralismentioning
confidence: 99%
“…Similarly, the ruling of Appeals Court of Thrace showed that managing mufti jurisdiction does not include parent-child relations though it includes the civil courts' purview (Tsavousoglou, 2015). The property relationship of the spousal is to be excluded from the mufti jurisdiction.…”
Section: Jurisdictional Competition and Internal Reformmentioning
confidence: 99%